(untitled) (European Journal of Child Development, Education and Psychopathology, 2021)
Introduction: Situations of peer bullying force to adopt moral positions among those who participate in them. The educational message of the school helps to form positions of inhibition or rejection of abuse. In addition, the leadership (presence)? of students through Support Systems is manifested as an effective prevention strategy for its prevention. Method: This research compares a sample of Spanish and Brazilian subjects, in schools with and without support systems who are asked for their moral positioning in front of two situations of bullying that show victims of different profiles, passive and provocative. Your answers are classified in different levels of moral quality. Results: The students who have peers support structures offer better moral positions. There are also better responses among Spanish students than in Brazilian ones. Conclusion: Promote peer support structures whit the students facilitate their moral growth in situations of bullying and is an effective preventive strategy to improve convivencia in schools.